2004
DOI: 10.1016/j.applanim.2004.05.004
|View full text |Cite
|
Sign up to set email alerts
|

Chronic increase of dietary l-tryptophan decreases gentle feather pecking behaviour

Abstract: Many studies show the involvement of the serotonergic (5-HT) system in the performance of abnormal behaviour in both human and animals. Recently, we showed that acute reduction of 5-HT turnover in the forebrain, increased gentle and severe feather pecking behaviour in chicks from a high (HFP) and low feather pecking (LFP) line of laying hens, suggesting that the performance of feather pecking behaviour involves low 5-HT neurotransmission.In the present study, we postulated that if low 5-HT is causally underlyi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
48
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(51 citation statements)
references
References 33 publications
2
48
1
Order By: Relevance
“…They suggest that detecting the same genetic markers in different populations implies that they are close to the functional mutation, which agrees with the theory of across-line association studies (Biscarini et al 2010). Therefore feather pecking in laying hens can seemingly be controlled by modulating their serotonergic system, by means of genetic selection or husbandry practices, either pharmacologically or dietary (van Hierden et al 2004a). Interestingly, the recent study by Bolhuis et al (2009) shows that genetic selection for low mortality, using the social models, leads to changes in the serotonergic system, already in the second generation of selection.…”
Section: Serotoninsupporting
confidence: 69%
See 2 more Smart Citations
“…They suggest that detecting the same genetic markers in different populations implies that they are close to the functional mutation, which agrees with the theory of across-line association studies (Biscarini et al 2010). Therefore feather pecking in laying hens can seemingly be controlled by modulating their serotonergic system, by means of genetic selection or husbandry practices, either pharmacologically or dietary (van Hierden et al 2004a). Interestingly, the recent study by Bolhuis et al (2009) shows that genetic selection for low mortality, using the social models, leads to changes in the serotonergic system, already in the second generation of selection.…”
Section: Serotoninsupporting
confidence: 69%
“…Substantial scientific evidence of the role of the serotonergic system in the development and modulation of feather pecking behaviour in laying hens has accrued over the last years (van Hierden et al 2002(van Hierden et al , 2004aBolhuis et al 2009). These studies related the occurrence of feather pecking with serotonin concentration and activity either in the brain or peripherally (circulatory system or peripheral nervous system), predominantly suggesting that lower levels of serotonin are associated with predisposition to perform feather pecking (van Hierden et al 2004a, b;Bolhuis et al 2009).…”
Section: Serotoninmentioning
confidence: 99%
See 1 more Smart Citation
“…Savory et al (1999) and v a n Hierden et al (2004b) found reduced feather pecking damage after L-tryptophan dietary supplementation, while diet with increased level of methionine and cystine did not have any significant effects on FP (Kjaer and Sörensen 2002). Increasing protein level in the diet had a positive effect on plumage and lowered FP and cannibalism.…”
Section: Nutritional Factorsmentioning
confidence: 96%
“…Tryptophan has already been proved to alleviate depression and aggression in humans (Mendelsohn et al, 2009) and animals. It has been shown that the supplementation of tryptophan may reduce aggression and alleviate stress in many species such as pigs (Henry et al, 1996;Koopmans et al, 2005Koopmans et al, , 2006Poletto et al, 2010;S eve et al, 1991) and chickens (Laycock and Ball, 1990;Rosebrough, 1996;Shea-Moore et al, 1996;Van Hierden et al, 2004). Tryptophan crosses the blood-brainbarrier via transporter proteins and acts as the precursor for 5-hydroxytryptamine (5-HT) synthesis in the serotonergic neurons.…”
Section: Introductionmentioning
confidence: 97%